Feasibility of Anterior Fixation with Single Screw for Odontoid Fractures in Pediatrics: A Computed Tomographic Study - Junyu Lin; Wei Ji; Zucheng Huang; Zhiping Huang; Qingan Zhu; Junhao Liu (Orthopaedic Surgery, 2023)
Objective Although it is an effective fixation technique for an unstable odontoid, anterior fixation remains challenging in pediatric populations. Our study measures the anatomical parameters of the odontoid to identify the feasibility of anterior fixation with a single screw for children. Methods We retrospectively collected data from 112 normal male and female children (aged between 2 and 18) in our institute from January 1, 2022 to December 31, 2022. Subjects were divided into a youth group (2–6 years old), a juvenile group (7–12 years old), and an adolescent group (13–18 years old). Sagittal and coronal computed tomography images of the upper cervical spine were used to measure the screw length, angle, and inner and outer diameters of the odontoid. One‐way analysis of variance with the Tukey test was used to analyze the parameters among the groups, while the t‐test was used to analyze gender differences. Correlations between parameters and age were assessed using Pearson's test. Results There were significant differences between male and female subjects in screw length and inner and outer diameters (of both sagittal and coronal views) but not in screw angle. The narrowest diameter of the odontoid was 4.0 ± 1.5 mm in the youth group, 5.5 ± 1.5 mm in the juvenile group, and 5.6 ± 1.1 mm in the adolescent group, respectively. There were significant differences among the three groups in screw length (p < 0.0001). The screw angle of the adolescent group was significantly smaller than that of the youth and juvenile groups. More than 90% of children aged 7–18 years old had an odontoid diameter greater than 4 mm, while only half of the youth group had an odontoid with diameter >4 mm. Screw length and inner and outer diameters in lateral view were positively correlated with age, and screw angle was negatively correlated with age. Conclusion It is feasible to insert a standard single screw (Φ 3.5 mm) into the odontoid of children aged 7–18 years old but not those aged 2–6 years old. How the anatomical parameters of the odontoid change with age, especially the narrowest diameters, is worthy of attention.